Sociolinguistics and Language History: The Helsinki Corpus of Early English Correspondence - Nevalainen, Terttu; Raumolin-Brunberg, Helena (HERMES - Journal of Language and Communication in Business, 2017)
The paper introduces our new project on diachronic sociolinguistics, focusing on the problems of compiling a representative corpus for this purpose. We study long-term linguistic change in the Late Middle and Early Modern English periods (1420-1680) in a computer-readable corpus of personal letters, which is designed specifically for the purposes of sociohistorical research. When completed, the Helsinki Corpus of Early English Correspondence will comprise some 1.5 million running words representing all the literate social ranks of the time, both sexes, and different ages and occupations. In our case, the issues that a corpus compiler must deal with include the coverage of all the sociolinguistically relevant categories of data, authenticity of extant materials, and the quality of editing.